The Ability of Computational Thinking in Physics Learning - Tantri Mugi Utami Rosandhi; Rudi Haryadi (Universitas Sebelas Maret, 2024)
The introduction describes the critical role of computational thinking in the digital era and ecosystem and developments in the global economy, work, and everyday life. Computational thinking skills are critical, especially in the Industrial Revolution 4.0 era, where technology and automation play a central role. Computational thinking includes problem solving, critical thinking, and integrating digital technology with human ideas. Abstraction, decomposition, algorithms, and evaluation are some of the main aspects of computational thinking skills. The research method used is a literature study with content analysis techniques. This research concludes that Computational Thinking is an approach that can improve the quality of physics learning, concept understanding, critical thinking skills, and student learning outcomes. Obstacles can be overcome by collaborating with other learning methods and approaches.